Part I – January 1968 - Papers - The Representation of the Textures of Rolled Copper, Brass, and Aluminum by BiaxiaI Pole Figures - R. O. Williams (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
The concept of biaxial pole figures which completely represent sheel textures is defined and an iterative least-squares solution given. The method has been applied to rolled copper, aluminum, and brass. The results show that the prior ideal textures are reasonably correct but incomplete. The major components in all three cases consist of a continuous range of orienta-tions roughly described as starting from (211) [111] continuing to (110) [112] to (110) [001], the details dif- THIS paper considers the problem of representing rolling textures in the most useful and comprehensible manner possible. A representation called a biaxial pole figure which completely represents such textures fering in all cases. For brass, in particular, the last part of the range is the most important. A minor cube component is established for the copper and aluminurn. The results were also analyzed by means of sets of three axial (inverse) pole figures to give similar, less-detailed results. The method of analysis is outlined. Such a representation is significantly less powerful than the biaxial method, but it has considerable utility in the calculation of anisotropic properties. is defined and an iterative least-squares solution is given. Such textures may be approximated by treating the principal directions as fiber axes to give three axial (inverse) pole figures. This representation is very useful for calculating anisotropic properties. New data for rolled copper, brass, and aluminum are given by both methods. In an axial pole figure the relative frequency or probability of a given physical direction (normally the